Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Collection of Selected Papers of the I International Conference on Information Technology and Nanotechnology 2015
DOI: 10.18287/1613-0073-2015-1490-112-121
|View full text |Cite
|
Sign up to set email alerts
|

Vibration resistance of headlight design for electric locomotive

Abstract: Abstract. I determined the natural frequencies of the headlight design for electric locomotive VL by software system of the finite-element analysis ANSYS. The obtained values of the natural frequencies are compared with the frequencies of the periodic vibrations experienced by the railway rolling stock. The analysis reveals the vibration frequencies determining the period of the trouble-free operation of the headlight.Keywords: headlight, electric locomotive, natural frequencies of design, trouble-free service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Real-life operation of locomotives and simulated experiments demonstrated that glass bottles of incandescent lamps and glass reflecting diffusers of railway searchlights feature short useful life throughout the entire vibration frequency range. Useful life of railway searchlights can be achieved by way of application of set of light-emitting diodes as light source 3 . Modern-day methods of designing lighting devices [4][5][6][7][8][9][10][11][12] , primarily light-emitting diode devices [13][14][15][16][17][18] , not only ensure long operating life but efficiency and the possibility to effectively shape the required directional pattern.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-life operation of locomotives and simulated experiments demonstrated that glass bottles of incandescent lamps and glass reflecting diffusers of railway searchlights feature short useful life throughout the entire vibration frequency range. Useful life of railway searchlights can be achieved by way of application of set of light-emitting diodes as light source 3 . Modern-day methods of designing lighting devices [4][5][6][7][8][9][10][11][12] , primarily light-emitting diode devices [13][14][15][16][17][18] , not only ensure long operating life but efficiency and the possibility to effectively shape the required directional pattern.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The aforesaid circumstances determined the design of the headlamp fixture and the number of light-emitting diodes placed on a flat baseplate, which substitutes the headlamp's glass reflecting diffuser (Fig. 1) 20,21 . The baseplate design was enhanced on the simulation in order to minimize its weight and make it the most rigid (deformation-resistant).…”
Section: Statement Of the Problemmentioning
confidence: 99%